CAZADORES-RECOLECTORES ESTEPARIOS EN LA DIVERSIDAD AMBIENTAL DEL NORTE DE AISEN CONTINENTAL DURANTE EL HOLOCENO TARDIO (VALLE DEL RIO CISNES,~44ºS)€€. - Reyes-Baez, Omar; Mendez Melgar, Cesar Augusto; Velasquez Moreno, Hector Bernardo; Quemada Lira, Claudia Monica; Trejo Vidal, Valentina Isel
12